Pengaruh Kepemimpinan Kepala Sekolah Dan Komunikasi Internal Terhadap Efektivitas Kerja Guru Di Smp Al-Manshuriyah Jakarta Barat - Idham; Hendro Risbiyantoro; Erna Tamiyati (Universitas Darunnajah Jakarta, Indonesia, 2023)
Abstract The effectiveness of the teacher's work will be created in accordance with the planned goals through a certain leadership style and internal communication within the organization that occurs between superiors and subordinates and subordinates and subordinates. This study used a sample of all teachers at SMP Al-Manshuriyah West Jakarta as many as 30 respondents. Data collection techniques using a questionnaire. This study aims (1) to determine the effect of principal's leadership on teacher work effectiveness, (2) to determine the effect of internal communication on teacher work effectiveness. (3) To determine how much influence the principal's leadership and principal's internal communication simultaneously has on effectiveness. teacher work. The results showed that there was a positive influence of principal's leadership on the work effectiveness of teachers by 13.9%, and 18.7% for the magnitude of the influence of internal communication on the effectiveness of teachers' work, as well as a simultaneous positive effect of 27.1%. And the rest is influenced by other factors outside this research.